2022
DOI: 10.1111/nph.18300
|View full text |Cite
|
Sign up to set email alerts
|

Pepper SUMO E3 ligase CaDSIZ1 enhances drought tolerance by stabilizing the transcription factor CaDRHB1

Abstract: Summary Small ubiquitin‐like modifier (SUMO) conjugation (SUMOylation) is a reversible post‐translational modification associated with protein stability and activity, and modulates hormone signaling and stress responses in plants. Previously, we reported that the pepper dehydration‐responsive homeobox domain transcription factor CaDRHB1 acts as a positive modulator of drought response. Here, we show that CaDRHB1 protein stability is enhanced by SUMO E3 ligase Capsicum annuum DRHB1‐interacting SAP and Miz dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Based on the potential association of CaPUB24 with various abiotic stresses, particularly drought stress (Figure 1C), we sought to elucidate the biological function of CaPUB24 in response to drought stress. For this investigation, we adopted the TRV‐based VIGS system (Burch‐Smith et al, 2004, Senthil‐Kumar and Mysore, 2014), which has been previously reported as an efficient strategy for gene silencing in pepper plants (Baek et al, 2021, Jeong et al, 2021, Joo et al, 2022, Bae et al, 2023, Jeong et al, 2023). We selected a suitable VIGS site using the SGN web tool (Fernandez‐Pozo et al, 2015) and generated CaPUB24 ‐silenced pepper plants using the TRV2: CaPUB24 construct.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the potential association of CaPUB24 with various abiotic stresses, particularly drought stress (Figure 1C), we sought to elucidate the biological function of CaPUB24 in response to drought stress. For this investigation, we adopted the TRV‐based VIGS system (Burch‐Smith et al, 2004, Senthil‐Kumar and Mysore, 2014), which has been previously reported as an efficient strategy for gene silencing in pepper plants (Baek et al, 2021, Jeong et al, 2021, Joo et al, 2022, Bae et al, 2023, Jeong et al, 2023). We selected a suitable VIGS site using the SGN web tool (Fernandez‐Pozo et al, 2015) and generated CaPUB24 ‐silenced pepper plants using the TRV2: CaPUB24 construct.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we identified the pepper JAZ gene transpirational water loss (Schroeder et al, 2001). Several studies have suggested that stomatal opening and closure critically influence drought sensitivity and tolerance (Joo et al, 2022;Xu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Under drought stress conditions, plants rapidly synthesize ABA in various organs, which subsequently enhances stomatal closure, inhibiting transpirational water loss (Schroeder et al, 2001). Several studies have suggested that stomatal opening and closure critically influence drought sensitivity and tolerance (Joo et al, 2022; Xu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The differently ubiquitinated proteins under high temperatures are enriched in a wide range of molecular functions Pengyan et al, 2020). Sumoylation can be stimulated in plants under heat (Miller et al, 2010;Miller et al, 2013;Hendriks and Vertegaal, 2016;Rytz et al, 2018;Han et al, 2021) or drought stress (Catala et al, 2007;Miura et al, 2009;Castro et al, 2012;Wu et al, 2016;Joo et al, 2022) and largely depends on SUMO E3 ligase SAP AND MIZ1 DOMAIN-CONTAINING LIGASE 1 (SIZ1). SIZ1 facilitates conjugation of SUMO to protein substrates, and positively regulates plant heat tolerance and acquired thermotolerance (Yoo et al, 2006;Kim et al, 2017;Rytz et al, 2018).…”
Section: Proteome Responses To Combined Heat and Droughtmentioning
confidence: 99%